Respiratory Syncytial Virus F Subunit Vaccine With AS02 Adjuvant Elicits Balanced, Robust Humoral and Cellular Immunity in BALB/c Mice - Zheng, Yu; Bian, Lijun; Zhao, Huiting; Liu, Yulan; Lu, Jingcai; Liu, Dawei; Zhang, Ke; Song, Yueshuang; Luo, Yusi; Jiang, Chunlai; Chen, Yan; Zhang, Yong; et al. (Frontiers in Immunology, 2020)
Respiratory syncytial virus (RSV) is a leading cause of lower respiratory illness, particularly in infants, the elderly, and immunocompromised adults. There is no licensed commercial vaccine against RSV. Importantly, formalin-inactivated RSV vaccines mediate enhanced respiratory disease. RSV fusion (F) protein with pre-fusion conformation is a promising candidate subunit vaccine. However, some problems remain to be solved, such as low immunogenicity and humoral immunity bias. Adjuvants can effectively enhance and adjust vaccine immune responses. In this study, we formulated pre-fusion RSV-F protein with the adjuvants, Alhydrogel, MF59, AS03, AS02, and glycol chitosan. We then conducted head-to-head comparisons of vaccine-induced immune responses in BALB/c mice. All adjuvanted vaccines enhanced antigen-specific and neutralizing antibody titers and viral clearance and gave an order of adjuvant activity: AS02 > AS03, MF59 > GCS and Alhydrogel. Among them, AS02 elicited the highest antibody expression, which persisted until week 18. Moreover, AS02 significantly enhanced Th1 type immune response in immunized mice. Mice in the AS02 group also showed faster recovery from viral attacks in challenge tests. Further transcriptome analysis revealed that AS02 regulates immune balance by activating TLR-4 and promotes Th1-type immune responses. These results suggest that AS02 may be an excellent candidate adjuvant for RSV-F subunit vaccines. This study also provides valuable information regarding the effect of other adjuvants on immune responses of RSV-F subunit vaccines.